THE APPLICATION OF THE DISCOVERY LEARNING MODEL TO IMPROVE STUDENTS' LEARNING OUTCOMES IN A SINGLE TIME UNIT - Ahmad Nasriadi; Selvia Zahara; Safrina Junita (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study is motivated by the low learning outcomes of students. The low learning outcomes are influenced by a lack of understanding of the learning material, which is caused by students' passive involvement in the learning process, such as lack of concentration, limited active participation, and an inability to relate the learning material to everyday life. The aim of this research is to improve learning outcomes by using the Discovery Learning model. This research is a quantitative study. The research method used is an experimental method, with the experimental design being a Pre-Experimental Design, specifically the One-Group Pretest-Posttest Design. This research was conducted at SD Negeri 2 Lamcot Aceh Besar. The population of the study consisted of all third-grade students at SD Negeri 2 Lamcot Aceh Besar, and the data were collected using Purposive Sampling. The sample consisted of 21 students selected from class III-A. Based on the results of the study, there was a significant improvement in students' learning outcomes before and after the intervention. The average pretest score was 53%, and after the treatment, the average posttest score increased to 83%. The conclusion drawn from this study is that the implementation of the Discovery Learning model can improve students' learning outcomes. Therefore, the use of the Discovery Learning model can be considered as one of the effective teaching methods to be applied in Mathematics learning.